STRATEGI MEMBANGUN BRAND IMAGEDALAM MENINGKATKAN DAYA SAING LEMBAGAPENDIDIKAN DI SMPIT AL-MAWADDAH WARRAHMAH KOLAKA - Andi Restu Fauziah Rustam; Nursyalim; Andi Faisal (Jurnal Teknologi Pendidikan Madrasah, 2025)
Building a brand image at SMPIT Al Mawaddah Warrahmah Kolaka is an effort made by schools to increase competitiveness among other educational institutions. In this case, this researcher knows about how an educational institution builds its brand image in the eyes of the public, various challenges faced by educational institutions, especially at SMPIT Al Mawaddah Warrahmah Kolaka, and the relationship between brand image and increasing competitiveness at SMPIT Al Mawaddah Warrahmah Kolaka. The method used in this study is to use a Qualitative approach with data collection methods by means of interviews, observations, and documentation. The resulting data is analyzed and then conclusions are made.